Comorbidity among Patients with Tuberculosis at AL Najaf Governorate - Zahraa Sabah Ibrahim; Khadija Shaban Hassan; Abbas Fadhal Humadi; Basim wajid Abollol Mahdi (Migration Letters, 2023)
Tuberculosis (TB), an infectious disease caused by Mycobacterium tuberculosis, is easily transmissible between individuals. Although its primary impact is on the lungs, TB can also affect various other organs such as the kidneys, spine, and brain. The disease spreads through the release of bacteria-laden droplets into the air when an infected person coughs, sneezes, or talks, leading to airborne transmission. Aim: This study aims to determine the prevalence of comorbidity in patients diagnosed with tuberculosis and those seeking treatment for chest illnesses in a consultant clinic. Method: A case-control study was conducted in a consultant clinic located in the al-Najaf Governorate. The study population comprised 356 individuals, with 118 individuals designated as cases and 236 individuals as controls. The data collection period spanned from January 2023 to April 2023. Results: The analysis revealed that individuals diagnosed with tuberculosis had an average age of 46.5 ± 18.28 years, while those in the control group had an average age of 47.8 ± 16.60 years. The statistical analysis yielded p-values of 0.04, 0.02, and 0.01 for different parameters such as malnutrition, severe kidney disease, and cough. Conclusion: This study provides insights into the prevalence of comorbidity among patients with tuberculosis and individuals seeking treatment for chest illnesses. The findings highlight variations in age distribution between the two groups and present significant p-values for specific parameters. These results contribute to a better understanding of the relationship between tuberculosis and comorbid conditions, emphasizing the importance of continued research and effective management strategies.